2019
DOI: 10.3390/geosciences9060255
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future: Using Long-Term Observational and Paleo-Proxy Reconstructions to Improve Model Projections of Antarctic Climate

Abstract: Quantitative estimates of future Antarctic climate change are derived from numerical global climate models. Evaluation of the reliability of climate model projections involves many lines of evidence on past performance combined with knowledge of the processes that need to be represented. Routine model evaluation is mainly based on the modern observational period, which started with the establishment of a network of Antarctic weather stations in 1957/58. This period is too short to evaluate many fundamental asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 173 publications
(226 reference statements)
1
22
0
Order By: Relevance
“…Kusahara and Hasumi (2013) conducted a series of idealized warming experiments and concluded that water masses flowing into ice shelf cavities differ greatly between Antarctic ice shelves and the changes in the inflowing water masses are responsible for the basal melt changes in the experiments. This study and all of the above studies clearly show that changes in coastal water masses over the Antarctic continental shelf are essential for understanding basal melt of Antarctic ice shelves, supporting the idea that the changes in Antarctic coastal water masses are one of the most important metrics for understanding Antarctic and Southern Ocean climates (Bracegirdle et al 2016).…”
Section: Summary and Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Kusahara and Hasumi (2013) conducted a series of idealized warming experiments and concluded that water masses flowing into ice shelf cavities differ greatly between Antarctic ice shelves and the changes in the inflowing water masses are responsible for the basal melt changes in the experiments. This study and all of the above studies clearly show that changes in coastal water masses over the Antarctic continental shelf are essential for understanding basal melt of Antarctic ice shelves, supporting the idea that the changes in Antarctic coastal water masses are one of the most important metrics for understanding Antarctic and Southern Ocean climates (Bracegirdle et al 2016).…”
Section: Summary and Discussionsupporting
confidence: 76%
“…Several studies have focused on the Antarctic iceocean interaction under present-day (i.e., the last few decades) and future conditions; however, no study has yet investigated the long-term evolution of the Southern Ocean ice-ocean interaction over the twentieth century. While the number of observations is limited in the beginning of the twentieth century, there exist some available observations and supporting evidence for the ocean and sea ice conditions in the Southern Ocean (Hobbs et al 2016b;Bracegirdle et al 2019). In other words, century-scale observational evidence, which consists of fragmented observations in the first half of the twentieth century and the more complete modern records, allows us to assess the model representation and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Since around 2000, the strong atmospheric warming trend along the Antarctic Peninsula has paused, although it is predicted to resume ( 11 ). Over the next century, the entire continent is expected to start to see climatic changes comparable to those recorded to date along the Antarctic Peninsula ( 12 , 13 ). The predicted “filling” of the ozone hole is likely to provide further positive feedback to this process.…”
Section: Introduction – Climate Change In Antarcticamentioning
confidence: 91%
“…For modeling past and future Antarctic climate, ice sheet stability, the thermohaline circulation, or the impacts of sea ice loss for ecosystems, data on past sea ice cover are crucial although barely available (Bracegirdle et al, 2015(Bracegirdle et al, , 2019. For the WAP, insights into climate and sea ice dynamics during the past 200 years are available from ice cores (stable isotopes, marine aerosols and snow accumulation), but information from high-resolution marine sediments and in particular sedimentary, geochemical or diatom-based sea ice proxies remains sparse .…”
Section: Introductionmentioning
confidence: 99%